Food Security Diplomacy: The Role of the Military in Regional Food Security - Wahyuni, Sri Wanda; Lathifatuddini, Lathifatuddini; Tofani, Ivan (Civil and Military Cooperation Journal, 2025)
This study examines the strategic role of the Indonesian military in food security and regional diplomacy. Using a qualitative literature review approach, the research highlights how the Indonesian Armed Forces (TNI) contribute to domestic food distribution during crises and serve as an instrument of soft power in regional food diplomacy. The findings reveal that the TNI’s logistical capacity, rapid mobilization, and involvement in humanitarian operations enhance Indonesia’s position within ASEAN and multilateral forums. However, risks remain, including civilian militarization, democratic dilemmas, and sustainability challenges if military involvement is not clearly regulated. The study concludes that military-based food diplomacy, when placed within transparent and accountable non-war operations, can become a strategic instrument for Indonesia in reinforcing regional stability and contributing to global human security.